Auto-Regulated Exercise Selection Training Regimen Produces Small Increases in Lean Body Mass and Maximal Strength Adaptations in Strength-trained Individuals. Issue 4 (April 2020) - Rauch, Jacob T.; Ugrinowitsch, Carlos; Barakat, Christopher I.; Alvarez, Michael R.; Brummert, David L.; Aube, Daniel W.; Barsuhn, Andrew S.; Hayes, Daniel; Tricoli, Valmor; De Souza, Eduardo O.
Abstract : Abstract: Rauch, JT, Ugrinowitsch, C, Barakat, CI, Alvarez, MR, Brummert, DL, Aube, DW, Barsuhn, AS, Hayes, D, Tricoli, V, and De Souza, EO. Auto-regulated exercise selection training regimen produces small increases in lean body mass and maximal strength adaptations in highly trained individuals. J Strength Cond Res 34(4): 1133–1140, 2020—The purpose of this investigation was to compare the effects of auto-regulatory exercise selection (AES) vs. fixed exercise selection (FES) on muscular adaptations in strength-trained individuals. Seventeen men (mean ± SD ; age = 24 ± 5.45 years; height = 180.3 ± 7.54 cm, lean body mass [LBM] = 66.44 ± 6.59 kg; squat and bench press 1 repetition maximum (1RM): body mass ratio 1.87, 1.38, respectively) were randomly assigned into either AES or FES. Both groups trained 3 times a week for 9 weeks. Auto-regulatory exercise selection self-selected the exercises for each session, whereas FES was required to perform exercises in a fixed order. Lean body mass was assessed via dual-energy X-ray absorptiometry and maximum strength via 1RM testing, pre-, and post-training intervention. Total volume load was significantly higher for AES than for FES (AES: 573, 288 ± 67, 505 kg; FES: 464, 600 ± 95, 595 kg, p = 0.0240). For LBM, there was a significant main time effect ( p = 0.009). However, confidence interval analysis (95% CIdiff ) suggested that only AES significantly increased LBM (AES: 2.47%, effect size [ES]: 0.35, 95% CIdiff [0.030–3.197 kg]; FES: 1.37%, ES: 0.21, 95% CIdiff [−0.500 to 2.475 kg]). There was a significant main time effect for maximum strength ( p ⩽ 0.0001). However, 95% CIdiff suggested that only AES significantly improved bench press 1RM (AES: 6.48%, ES: 0.50, 95% CIdiff [0.312–11.42 kg]; FES: 5.14%, ES: 0.43, 95% CIdiff [−0.311 to 11.42 kg]). However for back squat 1RM, similar responses were observed between groups (AES: 9.55%, ES: 0.76, 95% CIdiff [0.04–28.37 kg]; FES: 11.54%, ES: 0.80, 95% CIdiff [1.8–28.5 kg]). Our findings suggest that AES may provide a small advantage in LBM and upper body maximal strength in strength-trained individuals.